Transtheoretical model for behavior changes: an important tool when adopting active life - Álvarez, Carlos (2008)
Despite the worship of beauty that has ruled this globalized society and the importance of physical activity for the prevention of cardio-degenerative diseases (US.DHHS, 1996), sedentary behavior continues to increase in the population.  What strategies can be used by professionals of human movement to make the population physically active? It is at this point where the Transtheoretical Model appears as an innovative option that greatly surpasses the classic short-term biological interventions, which have focused on momentary changes produced by physiological values.  This model has great potential since it offers the theoretical basis that makes the acquisition of an active behavior possible.  This article explains the theoretical basis of the transtheoretical model, including the way to assess the stages of change and to develop different strategies to make the person active by using behavioral processes and processes of change.